STUDI EMPIRIS PENYERAPAN ANGGARAN DAN FAKTOR DETERMINASINYA PADA PEMERINTAH KOTA PEKANBARU - Wanda Hamidah; Yuneita Anisma; Devi Safitri (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
The purpose of this research is to find out the influence of budget planning, human resource competence, organizational motivation towards budgets in the regional organizations of the city of Pekanbaru. The research method used is a quantitative re`search method with primary data obtained from questionnaire data measured using a Likert scale. The study population was all Regional Organizations in the Government of Pekanbaru. This sample researchers are the chief of regional organizations, Chief of Subdivision and treasurer of expenditure at 43 regional organizations in Pekanbaru City selected using purposive sampling method. Data collection was carried out through a survey using a questionnaire that was distributed to respondents. This research uses multiple linear analysis method with SPSS version 22. The results of this study indicate that budget planning, human resource competencies, motivation, and organizational commitment affect budget absorption in Pekanbaru City Government